Hybrid luminescent porous silicon for efficient drug loading and release. Issue 11 (20th January 2017) - Ghafarinazari, A.; Scarpa, M.; Zoccatelli, G.; Comes Franchini, M.; Locatelli, E.; Daldosso, N.
Abstract : In recent decades, biocompatible and light emitting porous silicon (pSi) showed the possibility for use in biomedical applications. Abstract : In recent decades, biocompatible and light emitting porous silicon (pSi) showed the possibility for use in biomedical applications. Unfortunately, until now the biological applications of light-emitting pSi have been severely limited due the immediate surface oxidation of this nanostructured material, followed by loss of optical properties and degradation in aqueous solutions. In view of drug delivery, the red–ox activity of pSi damages the carried drug. Herein, we have investigated the stabilization of pSi microparticles in aqueous solution by covalent attachment of polymers to a short-chain organic coating grafted onto inorganic silicon. The morphological, chemical and optical stability obtained using polyethylene glycol confirm this biocompatible polymer as a superior shell matrix nanostructure for use in biological environments.